US Mayors’ and Health Commissioners’ Opinions About Health Disparities in Their Cities - Purtle, Jonathan (Am J Public Health, 2018)
Objectives. To characterize US mayors’ and health commissioners’ opinions about health disparities in their cities and identify factors associated with these opinions. Methods. We conducted a multimodal survey of mayors and health commissioners in fall–winter 2016 (n = 535; response rate = 45.2%). We conducted bivariate analyses and multivariable logistic regression. Results. Forty-two percent of mayors and 61.1% of health commissioners strongly agreed that health disparities existed in their cities. Thirty percent of mayors and 8.0% of health commissioners believed that city policies could have little or no impact on disparities. Liberal respondents were more likely than were conservative respondents to strongly agree that disparities existed (mayors: odds ratio [OR] = 7.37; 95% confidence interval [CI] = 3.22, 16.84; health commissioners: OR = 5.09; 95% CI = 3.07, 8.46). In regression models, beliefs that disparities existed, were avoidable, and were unfair were independently associated with the belief that city policies could have a major impact on disparities. Conclusions. Many mayors, and some health commissioners, are unaware of the potential of city policies to reduce health disparities. Ideology is strongly associated with opinions about disparities among these city policymakers. Public Health Implications: Information about health disparities, and policy strategies to reduce them, needs to be more effectively communicated to city policymakers.